(3fgGjI GdeQGe aj TQM eNJUQ GdCMcGes - (3GdYGedj, GdehShj, GdMGFQj, eMeO Ydj Hf CHj GdMSf Hf UGdM, J (B1290(3g`s ((3HfjGO Hf SjO ejQc GdMSjfjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3bhdg(B: (3cJGH GdfcGM, bGd GdLhgQj(B: (3GdfcGM GdhWF(B...s
(3BNQgG (B:s
(3hgh LjO deWGHbJg debJVi GdCUd GdSGde ef GdYGQV, hGddg JYGde CYde HMbGFb CMcGeg(B. (3hGdMeO ddg(B...s
(3JHUQI GdYfhGf (B:s
(3fgGjI GdeQGe aj TQM GdeNJUQ GdfGaYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B300s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B503s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis